Composite nanoparticles, solution, Pickering emulsion, preparation method and application thereof

Through the composite nanoparticles of tea residue protein and epigallocate gallate, the problem of instability of Pickering emulsion caused by cereal protein was solved, and a high stability, antioxidant and viscoelastic Pickering emulsion preparation was achieved.

CN116473219BActive Publication Date: 2025-03-14ANHUI AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310680144.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2025-03-14
Estimated Expiration
2043-06-08

AI Technical Summary

Technical Problem

Cereal proteins have a larger molecular mass and low solubility as Pickering particles, resulting in unstable Pickering emulsions, limiting their widespread use.

Method used

Complex nanoparticles were prepared by combining tea residue protein and epigallocate gallate through polar molecular interaction forces as emulsifiers to improve the stability of Pickering emulsion.

Benefits of technology

The prepared composite nanoparticles have the advantages of small particle size and high oxidation resistance. Pickering emulsion with high stability, oxidation resistance and viscoelasticity can be prepared as an emulsifier, which is effective as a food-grade stabilizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116473219B_ABST
    Figure CN116473219B_ABST
Patent Text Reader

Abstract

The present invention provides a composite nanoparticle, belonging to the technical field of food and biological preparations, wherein the composite nanoparticle comprises tea residue protein and epigallocatechin gallate; the mass ratio of the tea residue protein to epigallocatechin gallate is 1:(0.01-0.1). The present invention utilizes the combination of tea residue protein and epigallocatechin gallate through hydrogen bonding to form a relatively compact structure, thereby improving the functional properties of the tea residue protein and reducing the particle size of the composite nanoparticle; the composite nanoparticle can prepare a Pickering emulsion with high stability, therefore, the nanoparticles composited by tea residue protein and epigallocatechin gallate can effectively serve as a food-grade stabilizer for Pickering emulsion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of food and biological preparations, and in particular to a composite nanoparticle, a solution, a Pickering emulsion and a preparation method and application thereof. Background Art

[0002] Pickering emulsion is a new type of emulsion in which solid particles replace traditional organic surfactants to stabilize the emulsion system. Compared with traditional emulsions stabilized by surfactants, Pickering emulsions stabilized by food-grade particles show better storage stability.

[0003] The solid particles used to prepare food-grade Pickering emulsions include polysaccharide particles such as starch, cellulose, chitosan, protein particles, and small molecules. Compared with polysaccharide particles such as starch, protein particles have greater advantages, mainly manifested in: protein itself has high nutritional value; and protein itself has good functional properties, and no or only a small amount of surface modification is required. Protein particles are divided into plant protein particles and animal protein particles. Compared with animal protein particles, plant protein particles have the advantages of low cost, wide source, and low allergenicity. Cereals are a rich source of plant protein particles, such as zein particles, but as Pickering particles, the large molecular weight and low solubility of cereal protein can easily cause emulsion instability, limiting its wide application. Therefore, there is an urgent need for a suitable nanoparticle as Pickering particle to improve the stability of the emulsion. Summary of the invention

[0004] The object of the present invention is to provide a composite nanoparticle, a solution, a Pickering emulsion and a preparation method and application thereof. The composite nanoparticle provided by the present invention can be used as an emulsifier to prepare a Pickering emulsion with high stability.

[0005] The invention provides a composite nanoparticle, comprising tea residue protein and epigallocatechin gallate; the mass ratio of the tea residue protein to epigallocatechin gallate is 1:(0.01-0.1).

[0006] Preferably, the method for preparing the tea residue protein comprises the following steps:

[0007] Mixing tea residue and NaOH solution to obtain a mixture; separating the mixture into solid and liquid and taking the supernatant;

[0008] The pH value of the supernatant is adjusted to 3.5, and the precipitate is collected to obtain tea residue protein.

[0009] The present invention also provides a composite nanoparticle solution, which uses water as a solvent and comprises the composite nanoparticles described in the above scheme.

[0010] The present invention also provides a method for preparing the composite nanoparticle solution described in the above scheme, comprising the following steps:

[0011] Dispersing the tea residue protein in water to obtain a mixture;

[0012] The mixed material and epigallocatechin gallate are mixed to obtain a composite nanoparticle solution.

[0013] The present invention also provides a Pickering emulsion, comprising a composite nanoparticle solution and oil;

[0014] The composite nanoparticle solution includes the composite nanoparticle solution described in the above scheme or the composite nanoparticle solution prepared by the preparation method;

[0015] The volume ratio of the composite nanoparticle solution to the oil is (8:2) to (2:8).

[0016] Preferably, the mass concentration of the composite nanoparticles in the Pickering emulsion is 0.25 to 1.5 g / 100 mL.

[0017] The present invention also provides a method for preparing the Pickering emulsion described in the above scheme, comprising the following steps:

[0018] The composite nanoparticle solution is mixed with oil to obtain a mixture, and the mixture is ultrasonically crushed to obtain a Pickering emulsion.

[0019] Preferably, the power of the ultrasonic pulverization is 152-532W.

[0020] The present invention also provides the use of the composite nanoparticles described in the above scheme, or the composite nanoparticle solution, or the composite nanoparticle solution prepared by the preparation method, or the Pickering emulsion, or the Pickering emulsion prepared by the preparation method as an emulsifier and / or stabilizer.

[0021] The present invention also provides the use of the composite nanoparticles described in the above scheme, or the composite nanoparticle solution, or the composite nanoparticle solution prepared by the preparation method, or the Pickering emulsion, or the Pickering emulsion prepared by the preparation method in the preparation of food or biological preparations.

[0022] Compared with the prior art, the present invention has the following significant beneficial effects:

[0023] The present invention provides a composite nanoparticle, comprising tea residue protein and epigallocatechin gallate; the mass ratio of the tea residue protein to epigallocatechin gallate is 1:(0.01-0.1). The present invention utilizes tea residue protein and epigallocatechin gallate to combine through polar molecular interaction forces to prepare composite nanoparticles, thereby improving the functional properties of tea residue protein; the nanoparticles formed by the composite of tea residue protein and epigallocatechin gallate have the advantages of small particle size and high antioxidant properties, and can be used as an emulsifier to prepare a Pickering emulsion with high stability, antioxidant properties, and viscoelasticity. Therefore, the nanoparticles composited by tea residue protein and epigallocatechin gallate can be effectively used as a food-grade stabilizer for Pickering emulsions. The preparation method of the composite nanoparticles provided by the present invention is simple, easy to operate, low in cost, safe and efficient, and effectively reduces costs. The present invention fully and reasonably utilizes tea residue materials, and extracting tea residue protein will make the tea residue obtain higher utilization value. In addition, tea residue protein and epigallocatechin gallate are both environmentally friendly and renewable bio-based green materials, which are safe, non-toxic and have good biocompatibility, are beneficial to environmental protection and promote the efficient utilization of biomass resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 The particle size of the composite nanoparticles and their ability to scavenge DPPH and ABTS free radicals under different ratios of tea residue protein and EGCG; A is the particle size distribution diagram of the composite nanoparticles; B is the particle size of the composite nanoparticles and their ability to scavenge DPPH free radicals; C is the particle size of the composite nanoparticles and their ability to scavenge ABTS free radicals;

[0026] Figure 2 Fourier transform infrared spectra of TP, EGCG and TPENs (composite nanoparticles with mass ratios of TP and EGCG of 1:0.01 and 1:0.1, respectively);

[0027] Figure 3 The centrifugal stability of Pickering emulsion prepared under different conditions; A is the ratio of TP to EGCG; B is the concentration of composite nanoparticles; C is the water-oil ratio; D is the pH; E is the ultrasonic power.

[0028] Figure 4These are the microscopic images of Pickering when the water-oil ratio is 6:4 and 4:6; A is the microscopic image of Pickering when the water-oil ratio is 6:4; B is the microscopic image of Pickering when the water-oil ratio is 4:6;

[0029] Figure 5 The appearance of Pickering emulsions with different water-oil ratios and pH values, and the appearance of Pickering emulsions with different water-oil ratios and pH values ​​after storage for 30 days;

[0030] Figure 6 The scavenging ability of Pickering emulsions with different water-oil ratios and pH values ​​on DPPH free radicals;

[0031] Figure 7 The scavenging ability of Pickering emulsions with different water-oil ratios and pH values ​​on ABTS free radicals;

[0032] Figure 8 is the apparent viscosity of different Pickering emulsions at a water-to-oil ratio of 4:6;

[0033] Fig. 9 Viscoelastic properties of different Pickering emulsions at a water-to-oil ratio of 4:6. DETAILED DESCRIPTION

[0034] The invention provides a composite nanoparticle, comprising tea residue protein and epigallocatechin gallate; the mass ratio of the tea residue protein to epigallocatechin gallate is 1:(0.01-0.1).

[0035] In the present invention, the tea residue protein preferably includes commercially available tea residue protein or tea residue protein extracted by any one of an alkali method, an enzymatic method or a composite extraction method; more preferably, the preparation method of the tea residue protein includes the following steps: mixing tea residue and a NaOH solution to obtain a mixture, separating the mixture into solid and liquid and obtaining a supernatant; adjusting the pH value of the supernatant to 3.5, and collecting the precipitate to obtain the tea residue protein.

[0036] The invention firstly mixes tea residues and NaOH solution to obtain a mixture; and then separates the mixture into solid and liquid and takes the supernatant.

[0037] In the present invention, the tea residues preferably include tea residues produced by the production of tea beverages and other products or tea residues dried after soaking tea leaves in boiling water for 5 times. The drying temperature is preferably 65°C, and the drying is preferably based on drying to constant weight. In the present invention, the purpose of soaking the tea leaves in boiling water for 5 times is to remove polyphenols and some other water-soluble impurities.

[0038] Before mixing the tea residue with the NaOH solution, the present invention preferably further comprises pulverizing the tea residue, and the particle size of the tea residue after pulverization is preferably ≤80 mesh. In the present invention, the NaOH solution is preferably an aqueous NaOH solution; the concentration of NaOH in the aqueous NaOH solution is preferably 0.2-0.4 mol / L, and more preferably 0.3 mol / L. In the present invention, the mass volume ratio of the tea residue to the NaOH solution is preferably 1 g: (20-50) mL, more preferably 1 g: (20-40) mL, and more preferably 1 g: 30 mL.

[0039] In the present invention, the temperature for mixing the tea residue and the NaOH solution is preferably 80-100° C., more preferably 90° C.; the mixing time is preferably 1-2 h, more preferably 1.5 h.

[0040] In the present invention, the solid-liquid separation preferably includes centrifugation, the rotation speed of the centrifugation is preferably 8000 r / min, and the time of the centrifugation is preferably 10 min.

[0041] After obtaining the supernatant, the present invention preferably further comprises decolorizing the supernatant; the decolorizing treatment is preferably performed by adding H 2 O 2 The aqueous solution was placed for 24 hours; the H 2 O 2 The mass volume concentration of the aqueous solution is 4 g / 100 mL; the purpose of the decolorization treatment is to remove colored impurities in the solution.

[0042] After the decolorization treatment, the present invention adjusts the pH value of the supernatant to 3.5, collects the precipitate to obtain the tea residue protein.

[0043] In the present invention, the purpose of adjusting the pH value of the supernatant to 3.5 is to adjust the pH value of the solution to the isoelectric point of the protein to precipitate the tea residue protein.

[0044] In the present invention, the method of collecting the precipitate preferably includes centrifugation, the rotation speed of the centrifugation is preferably 8000 r / min, and the time of the centrifugation is preferably 10 min.

[0045] After collecting the precipitate, the present invention preferably further comprises drying the precipitate, and the drying preferably comprises freeze drying; the freeze drying is preferably carried out using a freeze dryer, the freeze drying time is preferably 48 hours, and the freeze drying temperature is preferably -80°C; finally, light green powdered tea residue protein is obtained.

[0046] In the present invention, the epigallocatechin gallate (EGCG) is purchased from Shanghai Yuanye Biotechnology Co., Ltd. In the present invention, the mass ratio of the tea residue protein to epigallocatechin gallate is preferably 1: (0.01-0.1), further preferably 1: (0.01-0.08), and more preferably 1: (0.04-0.08). At this mass ratio, the complex formed by the interaction of the tea residue protein and EGCG can effectively inhibit the aggregation between oil droplets, thereby improving the stability of the emulsion, and can improve the antioxidant properties of the composite nanoparticles.

[0047] The present invention also provides a composite nanoparticle solution, which uses water as a solvent and comprises the composite nanoparticles described in the above scheme.

[0048] The present invention also provides a method for preparing the composite nanoparticle solution described in the above scheme, comprising the following steps:

[0049] Dispersing the tea residue protein in water to obtain a mixture;

[0050] The mixed material and epigallocatechin gallate are mixed to obtain a composite nanoparticle solution.

[0051] The invention first disperses tea residue protein in water to obtain a mixture.

[0052] In the present invention, the water is preferably pure water; the mass volume ratio of the tea residue protein to water is preferably (1-4) g: 100 mL. After obtaining the mixture and before mixing the mixture with epigallocatechin gallate, the present invention preferably further comprises placing the mixture in a 4°C environment for 9-16 hours, more preferably 12 hours, to allow the TP to be fully hydrated, and when used, taking out the mixture and restoring the temperature to room temperature before use, the room temperature is preferably 20-30°C, more preferably 25°C.

[0053] After obtaining the mixture, the present invention mixes the mixture with epigallocatechin gallate to obtain a composite nanoparticle solution. In the present invention, the mixing is preferably based on the complete dissolution of epigallocatechin gallate; the mixing temperature is preferably 20-30°C, more preferably 25°C.

[0054] After the mixing, the present invention preferably further comprises adjusting the pH of the mixed solution to 3-11, more preferably 7-11, and more preferably 7. Under such pH conditions, the prepared composite nanoparticles can be effectively adsorbed at the oil-water interface, stabilize the Pickering emulsion without stratification, and have good centrifugal stability. The reagent used to adjust the pH of the solution is preferably 1 mol / L HCl aqueous solution and / or 1 mol / L NaOH aqueous solution.

[0055] After adjusting the pH of the mixed solution, the present invention preferably further comprises magnetically stirring the solution, wherein the rotation speed of the magnetic stirring is 800 r / min; the time of the magnetic stirring is 2 hours; the function of the magnetic stirring is to mix the tea residue protein with epigallocatechin gallate, and under the action of intermolecular forces dominated by hydrogen bonds, a relatively compact structure is formed, thereby reducing the particle size of the composite nanoparticles.

[0056] The present invention also provides a Pickering emulsion, comprising a composite nanoparticle solution and oil;

[0057] The composite nanoparticle solution includes the composite nanoparticle solution described in the above scheme or the composite nanoparticle solution prepared by the preparation method;

[0058] The volume ratio of the composite nanoparticle solution to the oil is: (8:2) to (2:8).

[0059] In the present invention, the oil preferably includes vegetable oil; the vegetable oil preferably includes soybean oil, peanut oil, sunflower seed oil or linseed oil.

[0060] In the present invention, the volume ratio of the composite nanoparticle solution to the oil is further preferably (6:4) to (4:6), more preferably 4:6 or 6:4. Under this volume ratio, the prepared Pickering emulsion is not easy to stratify and has good stability.

[0061] In the present invention, the mass concentration of the composite nanoparticles in the Pickering emulsion is preferably 0.25-1.5 g / 100 mL, more preferably 0.5-1.5 g / 100 mL, more preferably 1-1.5 g / 100 mL, and most preferably 1.5 g / 100 mL. At this mass concentration, the prepared emulsion has no obvious stratification, and only a little water phase is precipitated at the bottom.

[0062] The present invention also provides a method for preparing the Pickering emulsion described in the above scheme, comprising the following steps:

[0063] The composite nanoparticle solution is mixed with oil to obtain a mixture; the mixture is ultrasonically crushed to obtain a Pickering emulsion.

[0064] In the present invention, the mixing is preferably stirring; the stirring is preferably carried out by a high-speed disperser; the mixing time is preferably 1.5 to 2.5 minutes, more preferably 2 minutes. In the present invention, the mixing by a high-speed disperser is used to obtain a crude emulsion.

[0065] In the present invention, the power of the ultrasonic pulverization is preferably 152-532 W, more preferably 152-342 W, and more preferably 342 W; the ultrasonic pulverization time is 1.5-2.5 min, and more preferably 2 min. Under the ultrasonic conditions, an emulsion is obtained by ultrasonic energy impact, and the emulsion has good centrifugal stability and is not easy to stratify.

[0066] The present invention also provides the use of the composite nanoparticles or the composite nanoparticle solution or the composite nanoparticle solution prepared by the preparation method as an emulsifier and / or stabilizer.

[0067] In the present invention, when the composite nanoparticles are used as an emulsifier and / or stabilizer, the addition amount is preferably 0.75 to 1.5 g / 100 mL, more preferably 1.25 to 1.5 g / 100 mL. The composite nanoparticles have the advantages of small particle size and high antioxidant properties. The Pickering emulsion prepared by the composite nanoparticles as an emulsifier and / or stabilizer has high stability, antioxidant properties, and viscoelasticity.

[0068] The present invention also provides the use of the composite nanoparticles or the composite nanoparticle solution or the composite nanoparticle solution prepared by the preparation method in the preparation of food or biological preparations.

[0069] In order to further illustrate the present invention, a composite nanoparticle, solution, Pickering emulsion and preparation method thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0070] Example 1

[0071] Preparation of composite nanoparticle solution

[0072] (1) Preparation of tea residue protein

[0073] Take 100g of tea leaves, soak them in 5000mL of boiling water, repeat the soaking for 5 times, soak for 15min each time, then take out the tea leaves and put them into boiling water again, take the tea residue after the last soaking; dry the tea residue at 65℃ to constant weight, then crush the dried tea residue and pass it through an 80-mesh sieve to obtain tea residue powder;

[0074] The tea residue powder was dispersed in a 0.3 mol / L NaOH aqueous solution at a mass volume ratio of 1 g:30 mL, and centrifuged at 8000 r / min for 10 min to collect the supernatant. 4 g / 100 mL of H 2 O 2The aqueous solution was placed for 24 hours for decolorization; the pH of the decolorized supernatant was adjusted to 3.5, and the precipitate was obtained by centrifugation at a speed of 8000r / min for 10 minutes; the precipitate was placed in a freeze dryer at a temperature of -80°C for 48 hours to obtain a light green powdered tea residue protein (TP).

[0075] (2) Preparation of composite nanoparticle solution

[0076] Accurately weigh 1 g of TP and disperse it in 100 mL of pure water to obtain a tea residue protein solution, and then place the solution at 4 °C for 12 h to allow the TP to fully hydrate;

[0077] The TP solution was removed and the temperature was restored to 25°C. 0.08 g of epigallocatechin gallate (EGCG) powder was added and stirred continuously to completely dissolve the EGCG. The pH was then adjusted to 7 with 1 mol / L HCl aqueous solution and 1 mol / L NaOH aqueous solution. The mixture was magnetically stirred at a speed of 800 r / min for 2 h to obtain a composite nanoparticle solution.

[0078] Example 2

[0079] The mass ratio of TP and EGCG powders was 1:0;

[0080] Accurately weigh 1 g of TP prepared in Example 1, disperse it in 100 mL of pure water to obtain a tea residue protein solution, and then place the solution at 4°C for 12 h to fully hydrate the TP;

[0081] The TP solution was taken out and the temperature was restored to 25°C, and then the pH was adjusted to 7 with 1 mol / L HCl solution and 1 mol / L NaOH solution, and magnetic stirring was performed at a speed of 800 r / min for 2 h to obtain a tea residue protein aqueous solution.

[0082] Example 3

[0083] The mass ratio of TP to EGCG powder was 1:0.01, i.e., 1 g of TP was weighed and 0.01 g of EGCG powder was added;

[0084] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0085] Example 4

[0086] The mass ratio of TP and EGCG powders was 1:0.02;

[0087] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0088] Example 5

[0089] The mass ratio of TP and EGCG powders was 1:0.03;

[0090] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0091] Example 6

[0092] The mass ratio of TP and EGCG powders was 1:0.04;

[0093] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0094] Example 7

[0095] The mass ratio of TP and EGCG powders was 1:0.05;

[0096] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0097] Example 8

[0098] The mass ratio of TP and EGCG powders was 1:0.06;

[0099] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0100] Example 9

[0101] The mass ratio of TP and EGCG powders was 1:0.07;

[0102] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0103] Example 10

[0104] The mass ratio of TP and EGCG powders was 1:0.09;

[0105] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0106] Embodiment 11

[0107] The mass ratio of TP and EGCG powders was 1:0.1;

[0108] The rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1.

[0109] Example 12

[0110] The particle size, DPPH radical scavenging rate, and ABTS radical scavenging rate of the composite nanoparticles in the composite nanoparticle solutions of Examples 1, 3, 4, 6, 8, and 11 were measured, and the particle size, DPPH radical scavenging rate, and ABTS radical scavenging rate of the tea residue protein in the tea residue protein aqueous solution in Example 2 were measured.

[0111] (1) Particle size measurement

[0112] Particle size was measured using Mastersizer 2000 laser particle size analyzer.

[0113] (2) Determination of DPPH radical scavenging rate of composite nanoparticle solution and tea residue protein

[0114] DPPH free radical is a non-physiological free radical centered on nitrogen and is relatively stable. When there are antioxidant substances in the solution that provide hydrogen atoms, they will pair with the lone pair of electrons in the DPPH free radical, causing the solution to become lighter in color and gradually reduced.

[0115] The composite nanoparticle solutions prepared in Examples 1, 3, 4, 6, 8, and 11 and the tea residue protein aqueous solution in Example 2 were tested respectively. The samples were first diluted 100 times to obtain sample solutions. 3 mL of the sample solution was taken into a test tube, and then 3 mL of DPPH solution was added. The mixture was vortexed and placed in the dark for 30 min (25 ± 0.2 ° C). The absorbance was measured at 517 nm and recorded as A. 1 At the same time, mix 3 mL of sample solution with 3 mL of anhydrous ethanol, and do the same treatment as above. Measure the absorbance value, which is recorded as A. 2 . Mix 3 mL of DPPH solution with 3 mL of anhydrous ethanol, and do the same as above. Measure the absorbance value, which is recorded as A 0 Each sample has 3 parallel samples, and the scavenging rate of DPPH free radicals by composite nanoparticles and tea residue protein aqueous solution is calculated according to formula (1):

[0116]

[0117] (3) Determination of free radical scavenging rate of composite nanoparticles and tea residue protein ABTS

[0118] First, prepare ABTS solution: weigh 200 mg of ABTS and 68.8 mg of potassium persulfate, dissolve in 100 mL of deionized water, mix thoroughly, and place at room temperature and away from light for 14 hours to prepare ABTS stock solution. When using, take an appropriate amount of ABTS stock solution and dilute it with anhydrous ethanol so that the absorbance of the diluted solution at 734 nm is 0.7±0.02. The solution should be prepared and used immediately.

[0119] The composite nanoparticle solutions prepared in Examples 1, 3, 4, 6, 8, and 11 and the tea residue protein aqueous solution in Example 2 were tested respectively. The samples were diluted 100 times, 1 mL of the sample solution was taken into a test tube, 3 mL of ABTS solution was added, vortexed and mixed, and placed in the dark at room temperature for 5 min. The absorbance was measured at 734 nm and recorded as A 1 . Mix 1 mL of anhydrous ethanol and 3 mL of ABTS solution, and follow the same method as above, and record it as A0 Each sample has 3 parallel samples, and the scavenging rate of ABTS free radicals by composite nanoparticles and tea residue protein aqueous solution is calculated according to formula (2):

[0120]

[0121] The results are shown in Table 1 and Figure 1 As shown (Note: Figure 1 The lowercase letters (af) above the bars indicate significant differences between the groups (p<0.05). Figure 1 As shown in A, as the mass of EGCG increases, the particle size of the composite nanoparticles first decreases and then increases. The particle size of TP itself is 194nm, but after adding EGCG, the particle size of the composite nanoparticles is significantly reduced to 144, 152, 157, and 159nm at 1:0.02, 1:0.04, 1:0.06, and 1:0.08. This may be due to the inclusion of EGCG, which, at a lower level, induces the formation of a relatively compact structure between TP and EGCG. As the mass of EGCG continues to increase to 1:0.1, the particle size increases significantly to 207nm. One possible speculation is that the increase in EGCG concentration leads to a loose structure of the composite nanoparticles, which may be due to conformational changes caused by other interactions between TP and EGCG. It is also possible that excessive EGCG binds to the surface of β-lg through non-covalent interactions, resulting in micro-aggregation and the formation of a large number of binary composite materials.

[0122] Depend on Figure 1 It can be found from B and C that the composite nanoparticles have certain antioxidant activity in both DPPH and ABTS experiments, confirming the antioxidant properties of TP. With the increase of EGCG, the scavenging rate of the composite nanoparticles for DPPH and ABTS free radicals increased significantly, reaching the maximum value at a ratio of TP to EGCG of 1:0.08, and there was no significant change at 1:0.1, and the antioxidant activity would no longer increase. The enhanced antioxidant activity is attributed to the hydroxyl (OH) content in EGCG. Since EGCG has a strong electron and proton donor ability, it combines with TP, so that the TPENs composite particles show more excellent antioxidant activity.

[0123] By measuring the particle size and the scavenging rate of DPPH and ABTS free radicals, it was found that the addition of EGCG can reduce the particle size of the composite nanoparticles and improve the antioxidant activity. However, when the ratio of TP and EGCG exceeds 1:0.08, the particle size increases and the antioxidant activity reaches saturation and will no longer increase. Therefore, when the ratio of TP and EGCG is 1:0.08, the antioxidant effect is best.

[0124] Table 1 Particle size, DPPH free radical scavenging rate, and ABTS free radical scavenging rate of composite particles with different TP and EGCG ratios

[0125]

[0126] Note: Table 1 used t-test, and different superscript lowercase letters (af) in the columns indicated significant differences among the groups (p<0.05).

[0127] Embodiment 13

[0128] Fourier infrared measurement

[0129] 1. Test materials

[0130] TP prepared in Example 1, EGCG purchased from Shanghai Yuanye Biotechnology Co., Ltd., composite nanoparticles obtained by freeze-drying the composite nanoparticle solution in Example 3 (TPENs 1:0.01), and composite nanoparticles obtained by freeze-drying the composite nanoparticle solution in Example 11 (TPENs 1:0.1);

[0131] The freeze-drying method is to place the composite nanoparticle solution in a freeze dryer at -80°C for 48 hours.

[0132] 2. Test methods

[0133] Take 1 mg of the above test material and mix it with 200 mg of potassium bromide powder, then grind the mixture into fine powder, press it into tablets, and measure it with Fourier transform infrared spectrometer. The spectrum range is 4000~400cm -1 The resolution is 4cm -1 .

[0134] Test results

[0135] 4000~400cm -1 In the wave number range, the FTIR spectra of TP, EGCG and composite nanoparticles with different ratios are shown in Figure 2 The hydrogen bond band of tea residue protein is 3300.56 cm -1 However, the hydrogen bonds changed after the composite nanoparticles were formed. The peak values ​​of the composite nanoparticles of Example 3 (TPENs 1:0.01) and the composite nanoparticles of Example 11 (TPENs 1:0.1) were 3304.72 cm -1 、3385.45cm -1 The results showed that a hydrogen bond was formed between TP and EGCG, which may be due to the interaction between the amide group of aspartic acid in tea residue protein and the hydroxyl group in EGCG. -1The peaks in the range correspond to CH, CH 2 and CH 3 The symmetric / asymmetric vibration of the groups, as the proportion of EGCG increases, the CH and CH 2 and CH 3 The interaction bonds also move slightly, so the combination of EGCG and TP can enhance the CH, CH 2 and CH 3 The protein has an amide I band (1700-1600 cm -1 ) and amide II band (1550~1510cm -1 The amide I band is mainly caused by the stretching of CO. As the concentration of EGCG increases, the characteristic peak of the amide I band red-shifts from 1652.15 cm -1 Increased to 1655.03cm -1 The amide II band is mainly due to the bending vibration of the NH group and the stretching vibration of the CN group. Compared with single TP, the characteristic peaks of the composite nanoparticles are slightly red-shifted. Both amide I and amide II bands are related to the secondary structure of the protein. Therefore, the changes in the intensity and position of amide I and amide II indicate the change of the secondary structure after TP binds to EGCG. The formation of hydrogen bonds between the hydroxyl groups of EGCG and the CN or NH groups in the tea residue protein peptides may lead to the rearrangement of the protein peptides. These findings indicate that EGCG is successfully connected to TP, and there may be other intermolecular forces between them, such as electrostatic repulsion or hydrophobic interactions.

[0136] Embodiment 14

[0137] Preparation of Pickering emulsion

[0138] The composite nanoparticle solution in Example 1 and oil were mixed in a volume ratio of 1:1 to make the concentration of the composite nanoparticles in the Pickering emulsion 0.5 g / 100 mL, mixed in a high-speed disperser for 2 minutes, and then ultrasonically crushed in an ultrasonic cell crusher at a power of 342 W for 2 minutes to obtain a Pickering emulsion.

[0139] Embodiment 15

[0140] The tea residue protein aqueous solution of Example 2 and the composite nanoparticle solutions of Examples 3, 4, 6, 8 and 11 were used to prepare Pickering emulsions according to the preparation method of Example 14.

[0141] Example 16

[0142] The ratio of TP to EGCG was fixed at 1:0.08, and the rest of the composite nanoparticle solutions of different concentrations were prepared according to the preparation method of Example 1;

[0143] The water-oil ratio was fixed at 1:1, and according to the preparation method of Example 14, the composite nanoparticle solutions of different concentrations were prepared into Pickering emulsions with composite nanoparticle concentrations of 0.25 g / 100 mL, 0.75 g / 100 mL, 1 g / 100 mL, 1.25 g / 100 mL, and 1.5 g / 100 mL, respectively.

[0144] Embodiment 17

[0145] The ratio of TP to EGCG was fixed at 1:0.08, and the rest of the composite nanoparticle solutions of different concentrations were prepared according to the preparation method of Example 1;

[0146] The concentration of the composite nanoparticles was fixed at 0.5 g / 100 mL. According to the preparation method of Example 14, the composite nanoparticle solutions of different concentrations were prepared into Pickering emulsions with water-oil ratios of 8:2, 7:3, 6:4, 4:6, 3:7, and 2:8, respectively.

[0147] Embodiment 18

[0148] The pH of the tea residue protein solution and the EGCG mixed solution were adjusted to 3, 5, 9, and 11, respectively, and the rest of the composite nanoparticle solution was prepared according to the preparation method of Example 1;

[0149] The above composite nanoparticle solution was used to prepare Pickering emulsion according to the preparation method of Example 14.

[0150] Embodiment 19

[0151] Composite nanoparticle solutions were prepared according to the preparation method of Example 1, and the power of ultrasonic pulverization was adjusted to 152 W, 247 W, 437 W, and 532 W respectively;

[0152] The rest of the preparation was carried out according to the preparation method of Example 14 to prepare Pickering emulsion.

[0153] Embodiment 20

[0154] 1 mL of the emulsion samples of Examples 14 to 19 were taken into centrifuge tubes, and then centrifuged at 10000 r / min for 1 min, and then taken out and photographed to observe whether there was stratification or oil separation, and to analyze the centrifugal stability of the samples. Each sample had 3 parallel samples.

[0155] The results are as follows Figure 3 As shown in the figure, the results show that the centrifugation of Pickering emulsions with different TP and EGCG mass ratios is as follows Figure 3As shown in A in FIG, the centrifugal stability of the emulsion with the addition of EGCG is improved. This may be because the complex formed by the interaction between TP and EGCG can effectively inhibit the aggregation between oil droplets, thereby improving the stability of the emulsion. However, when the mass ratio of EGCG to TP and EGCG is 1:0.1, the centrifugal stability effect is reduced. It may be that excessive EGCG destroys the original structure. Combined with the conclusion of Example 12, the appropriate addition of EGCG can improve the antioxidant activity of the composite particles. Therefore, the preferred mass ratio of TP and EGCG is 1:0.08.

[0156] The effect of different solid particle concentrations on the centrifugal stability of Pickering emulsions is shown in Figure 3 B in the figure shows that as the solid concentration increases, the emulsion centrifugal stability becomes better. When the solid particle concentration is 0.25g / 100mL, the emulsion is obviously stratified after centrifugation and oil is precipitated. When the concentration is 0.5g / 100mL and 0.75g / 100mL, the emulsion stratification is more obvious and no oil is precipitated. When the concentration is 1g / 100mL, 1.25g / 100mL, and 1.5g / 100mL, the emulsion stratification is not obvious, and only a little water phase is precipitated at the bottom. The centrifugal stability is getting better and better, and the preferred solid particle concentration is 1.5g / 100mL.

[0157] The centrifugation diagrams of Pickering emulsions with different water-oil ratios are shown in Figure 3 In C, when the water-oil ratio is 8:2 and 7:3, the emulsion is obviously stratified, when the water-oil ratio is 6:4, the stratification is not obvious, when the water-oil ratio is 5:5, the stratification is obvious, when the water-oil ratio is 4:6, only a little water phase is precipitated at the bottom, and the stratification is not obvious. When the water-oil ratio is 3:7 and 2:8, the emulsion has poor centrifugal stability and the oil phase is completely precipitated, indicating that the maximum limit of the Pickering emulsion oil phase has been reached. Therefore, the water-oil ratio is preferably (6:4) to (4:6).

[0158] The centrifugation diagrams of Pickering emulsions with different pH values ​​are shown in Figure 3 D in the figure shows that when the pH is 3, the composite nanoparticles completely sink to the bottom, and the water phase and the oil phase are completely separated. When the pH is 5, the water phase and the oil phase are clearly separated. When the pH is 7, the separation is not obvious. When the pH is 9 and 11, there is no separation, and the centrifugal stability is good. This is because the composite nanoparticles are affected by the tea residue protein, and the isoelectric point of the tea residue protein is about 3.5. When the pH is 3 and 5, close to the isoelectric point of the protein, the repulsive force between the emulsion droplets is not enough to overcome the intermolecular forces, such as van der Waals force and hydrophobic force. The small emulsion droplets are unstable and aggregate into large emulsion droplets, resulting in the instability of the Pickering emulsion. The composite nanoparticles with a pH value of 7 to 11 can be effectively adsorbed at the oil-water interface to stabilize the Pickering emulsion. Therefore, the preferred pH values ​​are 7, 9, and 11.

[0159] The centrifugation diagrams of Pickering emulsions with different ultrasonic powers are shown in Figure 3As shown in the figure, when the power is 342W, the emulsion centrifugal stability is the best. If the power is too low, the composite particles cannot be completely mixed with water and oil to form a stable emulsion system. If the power is too high, the stable system of the emulsion will be destroyed, making the emulsion easier to separate. Therefore, the optimal ultrasonic power is 342W.

[0160] Embodiment 21

[0161] Observation of emulsion microstructure

[0162] Experimental method: The volume ratios of the composite nanoparticle solution and the oil were 6:4 and 4:6 respectively; the rest of the Pickering emulsion was prepared according to the optimal factors in Example 20. The microstructure of the emulsion was observed by optical microscopy.

[0163] The results are as follows Figure 4 As shown, the droplets under the two conditions are round, evenly distributed, and have a dense structure. The emulsion droplets with a volume ratio of composite nanoparticle solution to oil of 4:6 are smaller than those of 6:4, and the droplets are close to each other, with a denser structure.

[0164] Embodiment 22

[0165] Emulsion appearance and milking index test

[0166] Experimental method: The volume ratio of the composite nanoparticle solution to the oil was 6:4 and 4:6 respectively; based on the above volume ratio, the pH of the composite nanoparticle solution was set to 7, 9, and 11 respectively; the remaining 6 Pickering emulsions under the above conditions were prepared according to the optimal factors in Example 20. The appearance and creaming index of the emulsions were observed after storage for 30 days

[0167] See the appearance changes after 30 days of storage. Figure 5 As shown in the figure, when the newly prepared emulsion is dropped onto a tilted petri dish, it is found that the emulsion droplets with a volume ratio of 6:4 between the composite nanoparticle solution and the oil slide quickly and have good fluidity, while the emulsion with a volume ratio of 4:6 does not slide easily and has a viscous setting effect. After 30 days of storage, the emulsion with a volume ratio of 6:4 is obviously stratified, while the emulsion with a volume ratio of 4:6 can be inverted without stratification and has a good stability. This may be because the water-oil ratio of 4:6 is the water-oil volume ratio near the critical point of the emulsion phase inversion under this condition, so it has higher stability. The pH under this condition has no significant effect on the storage stability of the Pickering emulsion.

[0168] Embodiment 23

[0169] Experimental materials: The pH values ​​of the tea residue protein solution and the composite nanoparticle solution were 7, 9 and 11 respectively, and the volume ratios (water-oil ratio) of the composite nanoparticle solution and oil were 6:4 and 4:6 respectively; and 8 Pickering emulsions were prepared according to the optimal factors in Example 20, and were recorded as TPpH7, TPENPs pH7, TPENPs pH9 and TPENPs pH11 respectively.

[0170] Test method: According to the method of Example 12, the DPPH free radical scavenging rate and ABTS free radical scavenging rate of Pickering emulsion in 8 were measured.

[0171] The results are as follows Figure 6 , Figure 7 As shown in Table 2 (Note: Figure 6 , Figure 7 In the table, * represents significance, * represents p<0.05, ** represents p<0.01, and *** represents p<0.001). As shown in Table 2, the Pickering emulsion prepared by the tea residue protein solution has a certain antioxidant activity, but the Pickering emulsion prepared by the composite nanoparticle solution has a significantly higher scavenging rate of DPPH and ABTS free radicals than the emulsion prepared by the single tea residue protein solution. The interaction between EGCG and tea residue protein can give the tea residue protein a stronger antioxidant activity and increase the antioxidant activity of the emulsion. This may be because EGCG is a strong antioxidant, and its free radical scavenging activity is generated by the resonance stabilization of free radicals produced after oxidation. The composite nanoparticles combined with tea residue protein have antioxidant hydroxyl groups, so the antioxidant activity of the emulsion is enhanced. Under the fixed volume ratio of the composite nanoparticle solution and oil, as the pH gradually increases, the scavenging rate of the Pickering emulsion for DPPH and ABTS free radicals shows a downward trend, and the trends are similar under the two water-oil ratio conditions. Through inter-group comparison, it was found that the Pickering emulsion prepared from the composite nanoparticle solution had the strongest antioxidant activity at pH 7; the difference in the antioxidant properties of the Pickering emulsion under neutral and alkaline conditions may be due to the differences in the content and spatial structure of the grafted EGCG, or the pH may affect the properties of EGCG.

[0172] Table 2 DPPH and ABTS free radical scavenging rates of TPENPs emulsions at different water-oil ratios and pH conditions

[0173]

[0174] Note: The t-test was used, and different superscript lowercase letters (ad) in the columns indicated significant differences among the groups (p<0.05).

[0175] Embodiment 24

[0176] Experimental materials: The pH values ​​of the tea residue protein solution and the composite nanoparticle solution were 7, 9 and 11 respectively. The rest of the Pickering emulsions were prepared according to the optimal factors in Example 20 and were recorded as TP-7, TPENPs-7, TPENPs-9 and TPENPs-11 respectively.

[0177] Test method: Use a rotational rheometer to measure the rheology of the emulsion. Drop the sample onto the stage and rotate it for 0.1 to 100 seconds. -1 The apparent viscosity was analyzed at a shear rate of 0.1-100 rad / s and a shear strain of 1%. A frequency sweep was performed in the linear viscoelastic region to record G′ and G″.

[0178] The results are as follows Figure 8 , Fig. 9 As shown in Table 3 and Table 4, Figure 8 It can be seen that the viscosity of the emulsion decreases with the increase of shear rate. When the shear rate is low, the viscosity of the emulsion is large, and as the shear rate increases, the viscosity of the emulsion decreases. This is a typical shear thinning phenomenon in non-Newtonian fluids, proving that the emulsion is a pseudoplastic fluid. Under high shear rate, the oil droplets break, resulting in shear thinning; in addition, the interaction between the composite nanoparticles may also be destroyed. Under the same pH conditions, the viscosity of the emulsion prepared by the composite nanoparticle solution is higher than that of the emulsion prepared by the single tea residue protein solution. This shows that under certain conditions, EGCG can enhance the flocculation of emulsion droplets. When the pH increases from 7 to 11, the viscosity of the emulsion prepared by the composite nanoparticle solution gradually decreases. This may be because as the pH increases, the mutual repulsion between molecules increases, and the particles are not easy to collide and agglomerate. The composite particles in the emulsion will maintain a regular internal order when stationary. Because the internal resistance is low, it is difficult to hinder the flow of droplets, so it exhibits a lower viscosity. Fig. 9It can be seen that the G′ of all emulsions is greater than G″, indicating that the emulsion has formed a gel-like network structure dominated by elasticity. For the emulsions prepared from the composite nanoparticle solution and the single tea residue protein solution, the G′ and G″ values ​​increase with the increase of angular frequency. However, at the same frequency, the G′ and G″ of the emulsion prepared from the composite nanoparticle solution are greater than those of the emulsion prepared from the single tea residue protein solution under the same pH conditions, indicating that the former has stronger gelation. EGCG plays an important role. The formation of composite nanoparticles strengthens the covalent interaction between protein molecules and reinforces the gel network structure of the protein. In the emulsion system stabilized by composite nanoparticles, as the pH increases, G′ tends to decrease but the effect is not significant, indicating that the elastic properties do not change much. The gradual decrease in G″ indicates that the viscosity gradually decreases, which is consistent with the result of the change of viscosity with shear rate. All rheological results show that Pickering emulsions have shear thinning properties and pseudoplastic fluid behavior. Foods such as ice cream, soup and mayonnaise have pseudoplastic fluid flow characteristics. Therefore, the composite nanoparticles formed by the complexation of tea waste protein and EGCG can be used as an additive in liquid diet, thus paving the way for the value-added creation of cheaper tea waste.

[0179] Table 3 Apparent viscosity of different Pickering emulsions at a water-oil ratio of 4:6

[0180]

[0181]

[0182] Table 4 Viscoelastic properties of different Pickering emulsions at a water-oil ratio of 4:6

[0183]

[0184] Conclusion: If Figure 5 As shown, when the pH of the composite nanoparticle solution is 7, 9, and 11, the mass ratio of tea residue protein and epigallocatechin gallate in the composite nanoparticle solution is 1:0.08, the volume ratio of the composite nanoparticle solution and oil is (6:4) to (4:6), the concentration of the composite nanoparticles in the Pickering emulsion is 1.5 g / 100 mL, and the ultrasonic power is 342 W, the prepared Pickering emulsion has good centrifugal stability and the emulsion does not stratify; and the emulsion has strong antioxidant activity, shear thinning properties and pseudoplastic fluid behavior.

[0185] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A composite nanoparticle, characterized in that: It comprises tea residue protein and epigallocatechin gallate; the mass ratio of the tea residue protein to epigallocatechin gallate is 1:(0.01-0.08); The preparation method of the tea residue protein comprises the following steps: The tea residue and NaOH solution are mixed to obtain a mixture; the mixture is separated into solid and liquid to obtain a supernatant; the pH value of the supernatant is adjusted to 3.5, centrifuged, and the precipitate is collected to obtain the tea residue protein.

2. A composite nanoparticle solution, characterized in that: Water is used as solvent, and the composite nanoparticles according to claim 1 are included.

3. The method for preparing the composite nanoparticle solution according to claim 2, characterized in that: The following steps are involved: Dispersing the tea residue protein in water to obtain a mixture; The mixed material and epigallocatechin gallate are mixed to obtain a composite nanoparticle solution.

4. A Pickering emulsion, characterized in that including composite nanoparticle solutions and oils; The composite nanoparticle solution comprises the composite nanoparticle solution according to claim 2 or the composite nanoparticle solution prepared by the preparation method according to claim 3; The volume ratio of the composite nanoparticle solution to the oil is 4:6; The mass concentration of the composite nanoparticles in the Pickering emulsion is 1.0 to 1.5 g / 100 mL; The preparation method of the Pickering emulsion comprises the following steps: mixing the composite nanoparticle solution with oil to obtain a mixture, and ultrasonically crushing the mixture to obtain the Pickering emulsion; The pH of the composite nanoparticle solution is 7-11, and the power of the ultrasonic pulverization is 247-342W.

5. Use of the composite nanoparticles according to claim 1, the composite nanoparticle solution according to claim 2, or the composite nanoparticle solution prepared by the preparation method according to claim 3 in the preparation of an emulsifier and / or a stabilizer.

6. Use of the composite nanoparticles according to claim 1, the composite nanoparticle solution according to claim 2, or the composite nanoparticle solution prepared by the preparation method according to claim 3 in the preparation of food or biological preparations.

Citation Information

Patent Citations

  • Preparation process of polyphenol-soybean protein particle self-assembled Pickering emulsion

    CN111838396A

  • Preparation process of heat aggregation mediated tea polyphenol-soybean protein microsphere particles

    CN111838397A